Influence of Ovarian Follicle Sizes and Estrous Signs on Pregnancy Following Progesterone-Based Fixed Time Artificial Insemination in Water Buffaloes - Atabay, Eufrocina P.; Atabay, Edwin C.; dela Cruz, Carlito F.; R. Apolinario, Jhon Paul; S. Maylem, Excel Rio; Flores, Ester B. (Journal of Buffalo Science, 2023)
The objectives of the present study were to elucidate the importance of follicle sizes and estrous signs during Controlled Internal Drug Release-Synch-human Chorionic Gonadotropin (CIDR-Synch-hCG) protocol for Fixed Time Artificial Insemination (FTAI) and to evaluate their association with pregnancy in water buffaloes. Data from riverine buffaloes (n = 207) under the CIDR-Synch-hCG protocol were analyzed. Buffaloes were administered with Gonadotropin-Releasing Hormone (GnRH) with insertion of CIDR on Day 0. Prostaglandin (PGF2α) was given on Day 7 with the removal of CIDR. hCG was given on Day 9, and AI was performed on Day 10. Follicle measurements by ultrasonography were done on Days 0, 7, and 10, and follicle sizes on those days were categorized into I, II, and III. Estrus signs were taken on the day of AI. The pregnancy diagnosis was done on Day 30-35 post-AI. The average size of follicles in Category III is significantly higher than those of Categories I and II, regardless of the Days of the protocol. Pregnancy is significantly (P<0.001) associated with Pre-Ovulatory Follicle (POF) size and uterine tonicity on the Day of AI but not with follicle sizes on Days 0 and 7, nor with mucus discharge discharge (P>0.05). The overall pregnancy rate is 44.44% while performing AI with POF size ≥12.0 mm increased the probability of pregnancy rate to 56.25%. In conclusion, the present study demonstrated a follicle size-based CIDR-Synch-hCG protocol providing new fertility indicators to improve FTAI efficiency in buffaloes with huge application in other livestock species.